PENGARUH LATIHAN PANJAT TALI TERHADAP KEKUATAN OTOT LENGAN DAN BAHU ATLET KADET GULAT RIAU - Sitepu, Maydelse br; Slamet, Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this study was that the arm and shoulder muscle strength was lacking. This type of research is a type of experimental research to see the effects of this form of exercise. The purpose of this rope climbing exercise on the strenght of the muscles of the arms and shoulders of riau wrestling athlete cadet. Population in this research is athletes the cadet riau wrestling to 6 people son. The sampling technique is by using total sampling, in which the total population is sampled. Technique of taking data obtained from pre-test and posttest. Instrument in this research using Test of expanding dynamometer as tool to measure pull and push the muscles of the arms and shoulders. The analysis was performed using t-test. Based on the analysis and discussion of data, it can be concluded that there is a significant influence of rope climbing exercise on the strenght of the muscles of the arms and shoulders of riau wrestling athlete cadet as evidenced by Thitung of 14,705 and Ttabel 1,943. Means Thitung> Ttable. At ɑ = 0.05 level.Key Words: Rope climbing, strenght of the muscles arms and shoulders